2007
DOI: 10.1098/rsta.2007.2130
|View full text |Cite
|
Sign up to set email alerts
|

Modelling vortex-induced fluid–structure interaction

Abstract: The principal goal of this research is developing physics-based, reduced-order, analytical models of nonlinear fluid-structure interactions associated with offshore structures. Our primary focus is to generalize the Hamilton's variational framework so that systems of flowoscillator equations can be derived from first principles. This is an extension of earlier work that led to a single energy equation describing the fluid-structure interaction. It is demonstrated here that flow-oscillator models are a subclass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The fundamentals of VIV have been well documented for a cylinder whose axis in quiescient fluid is perpendicular to the oncoming flow (normal incidence case), the body being either rigid and elastically-mounted (King et al 1973;Bearman 1984Bearman , 2011Naudascher 1987;Mittal & Tezduyar 1992;Hover et al 1998;Okajima et al 2002;Sarpkaya 2004;Williamson & Govardhan 2004;Klamo et al 2006;Leontini et al 2006;Benaroya & Gabbai 2008;Lucor & Triantafyllou 2008;Dahl et al 2010;Navrose & Mittal 2013;Cagney & Balabani 2014;Konstantinidis 2014) or flexible (Trim et al 2005;Chaplin et al 2005;Lie & Kaasen 2006;Lucor et al 2006;Huera-Huarte & Bearman 2009, 2014; Vandiver et al 2009;Modarres-Sadeghi et al 2011;Bourguet et al 2011aBourguet et al ,b, 2012Bourguet et al , 2013a. VIV naturally appear both in the cross-flow direction and in the in-line direction, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamentals of VIV have been well documented for a cylinder whose axis in quiescient fluid is perpendicular to the oncoming flow (normal incidence case), the body being either rigid and elastically-mounted (King et al 1973;Bearman 1984Bearman , 2011Naudascher 1987;Mittal & Tezduyar 1992;Hover et al 1998;Okajima et al 2002;Sarpkaya 2004;Williamson & Govardhan 2004;Klamo et al 2006;Leontini et al 2006;Benaroya & Gabbai 2008;Lucor & Triantafyllou 2008;Dahl et al 2010;Navrose & Mittal 2013;Cagney & Balabani 2014;Konstantinidis 2014) or flexible (Trim et al 2005;Chaplin et al 2005;Lie & Kaasen 2006;Lucor et al 2006;Huera-Huarte & Bearman 2009, 2014; Vandiver et al 2009;Modarres-Sadeghi et al 2011;Bourguet et al 2011aBourguet et al ,b, 2012Bourguet et al , 2013a. VIV naturally appear both in the cross-flow direction and in the in-line direction, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These ad hoc methods are outside of the scope of this work that is focused on first principles models, specifically, using variational principles. Reviews of the empirical models can be found in [2], [6] and [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed the monofrequencyas well as multi-frequency vortex-induced vibration of a tensioned beam immersed in a linear shear flowand free to move in both the in-line and cross-flow directions, using direct numerical simulation (Bourguet, Lucor, & Triantafyllou, 2012). A reduced-order analytical model of nonlinear fluid-structure interactions was alsodeveloped by using the Hamilton's principle and Navier-Stokes equations (Benaroy & Gabbaia, 2008;Gabbaia & Benaroy, 2008). A similar study built a general low-order fluid-structure interaction model capable of evaluating themulti-mode interactions in vortex-induced vibration of flexible curved/straight structures (Srini, 2010).…”
Section: Vortex-induced Vibrationmentioning
confidence: 99%
“…General reduced-order, analytical models of nonlinear flow-oscillator interactions were developed by usingHamilton's variational formulation coupling Navier-Stokes equations (Benaroy & Gabbaia, 2008;Gabbaia & Benaroy, 2008). Many wake-body models are shown to be recoverable from the more general model derived byexplicit assumptions.…”
Section: Previous Models and Their Limitationsmentioning
confidence: 99%